Control of the Fluid Viscosity in a Mock Circulation. Issue 1 (17th July 2017) - Boës, Stefan; Ochsner, Gregor; Amacher, Raffael; Petrou, Anastasios; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: A mock circulation allows the in vitro investigation, development, and testing of ventricular assist devices. An aqueous‐glycerol solution is commonly used to mimic the viscosity of blood. Due to evaporation and temperature changes, the viscosity of the solution drifts from its initial value and therefore, deviates substantially from the targeted viscosity of blood. Additionally, the solution needs to be exchanged to account for changing viscosities when mimicking different hematocrits. This article presents a method to control the viscosity in a mock circulation. This method makes use of the relationship between temperature and viscosity of aqueous‐glycerol solutions and employs the automatic control of the viscosity of the fluid. To that end, an existing mock circulation was extended with an industrial viscometer, temperature probes, and a heating nozzle band. The results obtained with different fluid viscosities show that a viscosity controller is vital for repeatable experimental conditions on mock circulations. With a mixture ratio of 49 mass percent of aqueous‐glycerol solution, the controller can mimic a viscosity range corresponding to a hematocrit between 29 and 42% in a temperature range of 30–42°C. The control response has no overshoot and the settling time is 8.4 min for a viscosity step of 0.3 cP, equivalent to a hematocrit step of 3.6%. Two rotary blood pumps that are in clinical use are tested at different viscosities. At a flow rate of 5 L/min, both show a deviation of roughly 15 and 10% in motor current for high rotor speeds. The influence of different viscosities on the measured head pressure is negligible. Viscosity control for a mock circulation thus plays an important role for assessing the required motor current of ventricular assist devices. For the investigation of the power consumption of rotary blood pumps and the development of flow estimators where the motor current is a model input, an integrated viscosity controller is a valuable contribution to an accurate testing environment.